OPEN THE AFL-CIO ARCHIVES ON INTERNATIONAL LABOR OPERATIONS - Scipes, Kim (La Sociología en sus Escenarios, 2010)
<!–[if gte mso 9]> María Eugenia de la O / Alejandro Canales 12.00 <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Abstract. Ordering the arrest of Chile’s former dictator, Augusto Pinochet, for violations of Spanish citizens’ human rights while they were in Chile during his rule, a Spanish judge opened a new front in the worldwide struggle for human rights in the Fall of 1998. British police carried out the order, arresting Pinochet who was in Britain at the time for a back operation. The subsequent decision by the British Law Lords that Pinochet was not protected from prosecution because he had been head of government during the time the alleged tortures and killings had taken place–they ruled that these activities were not a normal part of the duties of a head of state–meant that he could be extradited to Spain to face the charges. The Blair government’s decision to permit Pinochet’s extradition only reinforced the High Court’s ruling, effectively establishing the principle that violating human rights is not a legally protected activity even for heads of state.